Simulasi parameter geometri regenerator mesin termoakustik - Nurpatria, N.; Syahrul, S.; Pandiatmi, P.; Sayoga, I.M.A.; Mulyanto, A. (Universitas Mataram, 2019)
The utilization potentials of biomass energy in Indonesia is very large. As modeled in this paper, the energy carrier flue gas from biomass combustion in the form of heat and temperature is applied as thermodynamic source for the thermoacoustic engine model. Therefore, 33 different models were constructed, modified, and tested in DELTA-EC software simulation in order to reveal their capability. The performance based on the criterion of their acoustic power output and efficiency in a set of various combination of two regenerator geometry parameters applied, radial cross-sectional area and length. The simulation results show that greater the cross-sectional area, greater the acoustic power and engines efficiency. The smallest regenerator size is at 80 mm2 cross-sectional area and 54 mm length, generates acoustic power of 5.812 W with its corresponding efficiency of 0.686%. While the biggest regenerator in volume at 120 mm2 and 165 mm in size, be able to amplified acoustic power up to 22.810 W with efficiency of 2.693%. An engine model with the highest performance produces acoustic power of 25.848 W and efficiency of 3.051%. This model uses an optimal regenerators dimension with 120 mm2 area at length of 150 mm.